P106 Successful outcome of the transitional process of inflammatory bowel disease from paediatric to adult age: a 5-year experience. (25th January 2019) - Testa, A; Nardone, O M; Giannetti, E; Rispo, A; Rea, M; Scarpato, E; Opramolla, A; Imperatore, N; Di Luna, I; Staiano, A M; Castiglione, F
Abstract: Background: The transitional process of young patients affected by inflammatory bowel disease (IBD) from pediatric to adult care is a crucial step. Our study aimed to investigate the 1-year success outcome of the transitional process of IBD patients. Methods: From 2013 to 2018, we evaluated the transitional process of patients with Crohn's disease (CD) or ulcerative colitis (UC), from the Pediatric to the Adult IBD Center. For each patient, the following parameters 12 months before and 12 months after the transition were evaluated: body mass index (BMI), disease activity and smoker status, number of outpatient visits and the pharmacological therapy, the number of disease exacerbations, hospitalisations, and surgical interventions. Results: We enrolled 106 patients with IBD (43 CD and 63 UC). No statistically significant difference was found between patients' BMI before and after transition. There was a significant reduction in the number of exacerbations and hospitalisations in the 12 months post-transition (pre-transition exacerbations: 0.74 ± 0.79, post-transition exacerbations: 0.35 ± 0.57, p < 0.001; pre-transition hospitalisations: 0.28 ± 0.44, post-transition hospitalisations: 0.1 ± 0.3, p < 0.001). In contrast, there was no significant difference in the number of outpatient visits (3.40 ± 1.4 vs. 3.25 ± 1.2; p = ns) and of patients undergoing surgery (0.9% vs. 1.8%, p = ns). We also found a significant difference ( p < 0.01) in the use of nutritional therapy between the pre-transition (18.8%) and the post-transition phase (0%). Moreover, in the post-transition period there was a reduction in immunosuppressant use (methotrexate: 9% vs. 2%, p = 0.03; azathioprine: 36% vs. 23%, p < 0.01). Conclusions: The parameters used as success indicators of the transition Programme confirm the achievement of a continuity of care from Pediatrics to adult Gastroenterology, such as the maintenance of a state of well-being, in a generally critical phase of the natural history of IBD patients.